Pengembangan Usaha Kain Endek di Denpasar 1975-2015 - Ariani, Ni Made; Suwitha, Putu Gede; Ayu Rai Wahyuni, Anak Agung (Humanis, 2016)
T he developing program of Endek in Denpasar is begun since the first Bali Art Festival is held for the first time in 1979 and endek become an office dresscode in 1990 . In the 1980's, endek reach its glory in Bali Province which centered in Klungkung Market, Badung market and Kumbasari. The Development of Endek is continued by Mayoress Selly Dharmawijaya Mantra for the Traditional Cloth's revitalisation and developing endek that well known by the society. Endek is developed because its a cultural heritage from the ancestors which full of philosophical meaning.